Chapter 5.40 The Profession of Research Management and Administration in the UK - Simon Kerridge (Emerald Publishing Limited, 2023)
This chapter outlines the circumstances that led to the evolution of the profession of research management and administration (RMA) in the UK, including some of the important drivers. While it is presented in the context of the UK research ecosystem as a whole, this is provided through a university lens as more is known about RMAs in this environment. It also provides a snapshot of the current UK RMA workforce: they are predominantly female and highly educated. With professional certification on the rise, we can see that the profession is developing, and it is argued that RMA professionals can play a pivotal role in research and development.
10.1108/978-1-80382-701-820231075; 10.1108/978-1-80382-701-820231075; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262